How to monitor the acclimatization of micropropagated plants - From in vitro to the field? - Osório, Maria Leonor (2015)
The high mortality experienced by plants during ex vitro transplantation stage is the major bottleneck in large scale application of micropropagation. The abnormal physiological and anatomical characteristics of micropropagated plantlets require that they should be gradually acclimatized to the environment of the greenhouse or field. Environmental factors, especially relative humidity and irradiance, play a critical role in both physiological and biochemical functions, namely water relations, gas exchange, photosynthetic efficiency and water oxidation, during transition from in vitro to ex vitro conditions. Throughout this period of transition and acclimatization substantial changes in those characteristics are necessary to achieve a successful micropropagation. This adaptation should be accurately monitored using relevant physiological parameters including pigment content, chlorophyll a fluorescence imaging, net photosynthetic rate, transpiration rate, and stomatal conductance. Growth traits and oxidative stress markers, such as electrolyte leakage, lipid peroxidation and hydrogen peroxide content, should be also analyzed. These parameters must be assessed during the course of ex vitro acclimatization in several periods and compared with those of plants growing in their natural habitat. The performance plants of Tuberaria major, an endangered species endemic from the Algarve region (Portugal), during their acclimatization through indoor-to-outdoor conditions was monitored using several physiological and biochemical traits as indicators. In view of the results, we concluded that the transplantation protocol described can be used for restoration purposes, contributing to the preservation of the species. © ISHS 2013.